The Conceptual Integration of Quality Function Deployment and Value Engineering for Product Development: A Case Study of Water Dispenser - Rosnani Ginting; Rinaldi Silalahi; M. Alwi Marunduri (International Journal of Technology)
Nowadays, product development is crucial for ensuring the survival of products in the market. This article focuses on the redesign of water dispenser products based on consumer problems and desires. It aims to provide products at real prices that align with customers' perceived value. Improvements were made using the integration of the Quality Function Deployment and Value Engineering methods. QFD is used to obtain attributes of customer needs and prioritize technical requirements and critical parts. Meanwhile, the VE method aimed to enhance product value and reduce costs based on the priority improvements identified through the QFD method. QFD Phase 1 gives priority to the technical requirements, which are durability, and QFD Phase 2 gives priority to critical parts, namely hoses, and thermostats. Then, based on the results of the QFD, improvements were made with VE, resulting in a type of water dispenser hose that was originally silicon that was substituted for polyethylene with a savings of 0.25 USD and a type of thermostat that initially reset KSD 301 that was substituted for a bakelite thermostat with a savings of 0.14 USD. The total cost savings is 0.38 USD or 26.54%.